Development of a Non-Destructive Technique For Assessing Internal Quality of Sapodilla Fruit - Ibrahim, Ab. Aziz (2001)
Non-destructive techniques (NDT) by impact response using Kiwifirm device and colour communicator using Chromameter against intrusive method using Steven QTS 25-texture meter were used to evaluate the ripeness of sapodilla fruit var. Subang. Kiwifirm score correlated well with the Steven QTS 25-texture analyser, whereas colour communicator did not detect any significant changes during ripening of the fruit. Kiwifirm value of 2.7, which is equivalent to 1750 g hardness, gave an indication of suitable stage for the fruit to be consumed. The value below 1.5 indicated that the fruit was overriped. Non-destructive technique using Kiwifirm device is also able to predict the storage life and the internal quality of sapodilla. Sapodilla fruit with the Kiwifirm score of below 6.0 at harvest was more acceptable by the sensory panellist. Fruits with a score of 6.1 to 7.0 could be stored for a longer period; however, the quality was not so good compared to those fruits having Kiwifirm score of below 6.0 at harvest. Fruits having Kiwifirm score of below 4.5 ripened within 1-3 days after harvest, thus were not suitable for storage. No significant difference was observed in the colour notation system (L*, a* and b*) with fruit ripeness. Kiwifirm device was found to be useful in detecting the stage of maturity of sapodilla fruit, predicting the quality and also the period at which the sapodilla fruit ripens. The power line (Y=O.02x3.6026), which was derived from the relationship of score resultant from the impact response of Kiwifrrm device and days taken for the fruit to ripen, can be used as a chart to predict and separate the fruit according to the predicted storage duration. Thus the technique can be used to group the fruits into either storage-marketing and utilization purposes, or only suitable group for certain markets. This strategy can be used to promote sapodilla fruits for distant market or export purposes. Postharvest losses, which occurred during storage and transportation, can be minimized.